Edukasi Kesehatan Reproduksi sebagai Upaya Peningkatan Kesehatan Reproduksi Remaja di SMA Negeri 2 Kendari - Asdhar, Ahmad; Ramadhani, Asmiranda; Pratiwi, Rahma Ayu; Aisyah, Sabrina Nurul; Kasmin, Shofiyah; Sulfiatri, Sulfiatri; Yunita, Yunita; Bahar, Hartati; Effendy, Devi Savitri; Muchtar, Febriana; Lestari, Hariati; Tosepu, Ramadhan (Pakis Journal Institute, 2025)
Reproductive health refers to the state of physical, mental, and social well-being related to the functions and systems of the human reproductive system. According to data from PKBI, approximately 15% of adolescents aged 10 to 24 years have had sexual intercourse outside of marriage. This is typically triggered by a strong curiosity about one's sexuality. Data obtained from the Prevention and Control of Communicable Diseases Unit (P2PM) of the Kendari City Health Department in 2023 recorded 283 cases of HIV/AIDS. This situation highlights the importance of appropriate educational interventions to enhance adolescents' understanding of maintaining reproductive health. This activity aims to increase knowledge about the importance of maintaining reproductive health by involving 26 students from SMAN 2 Kendari as a pilot class. The activity employed interactive lectures and the educational game “Ranking 1.” Evaluation was conducted through pre-tests and post-tests. The results showed that the average pre-test score was 95 (SD = 6.56), while the post-test showed an increase to 97 (SD = 5.08). However, the changes observed did not show statistical significance (p=0.219). Nevertheless, every respondent (100%) showed a good level of knowledge from the pre-test to the post-test. These findings indicate that educational programs can contribute to maintaining students' high level of knowledge regarding reproductive health.